Comparative Study of the Use of Objective Tests and T essays D in Improving Achievement Learning Indonesian Language - Sutarno, Sutarno; Hernawati, Sri Purni (Universitas Negeri Makassar, 2022)
Educational institutions in Indonesia , so Indonesian is included as one of the fields of study that is taught from elementary school to university, so that the success of its teaching will determine its further development. To find out success can be done in various ways, including through assessment or evaluation activities, both orally and in writing. In general, what teachers do at school is a written test consisting of an objective test and an essay test. The population taken in this study were students of class s XI AK and class XI TKJ. The data collection technique used is the experimental method and the test method, because basically this research will compare two forms of objective tests and essay tests for class XI students of SMK Gita Kirtti I Jakarta. While other methods are helpful. The hypothesis in this research is that learning achievement in Indonesian using objective tests is better than those using essay tests for class XI students at SMK Gita Kirtti I Jakarta for the 2020/2021 academic year. Analysis of the data used is statistical processing techniques, using the t test formula. After the two data obtained are entered into the formula, it can be seen that to = 3.037 with a significance level of 5% t table = 2.093. Meanwhile, with a significance level of 1% t table = 2.861. This means that to is greater than t table, so the hypothesis can be accepted. Thus, it can be concluded that learning achievement in the field of Indonesian language studies by evaluating the form of an objective test is better than the evaluation of the form of an essay test for class XI students of SMK Gita Kirtti I Jakarta.